1991
DOI: 10.1590/s0074-02761991000600025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of azadirachtin in Rhodnius prolixus: data and hypotheses

Abstract: The effects of azadirachtin A, a tetranortriterpenoid from the neem tree Azadirachta indica J., on both development and interaction between Trypanosoma cruzi, the causative agent of Chagas' disease, and its vector Rhodnius prolixus were studied. Given through a blood meal, a dose-response relationship of azadirachtin was established using antifeedant effect and ecdysis inhibition as effective parameters. A single dose of azadirachtin A was able to block the onset of mitosis in the epidermis and ecdysteroid tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Azadirachtin is a natural compound that has been used to inhibit the development of PMVM, affecting several aspects of insect's physiology such as the adhesion of T. cruzi epimastigote forms in the midgut (Garcia et al, , 1991Nogueira et al, 1997;Gonzales et al, 1998). Based on the data shown in Fig.…”
Section: Meanmentioning
confidence: 99%
“…Azadirachtin is a natural compound that has been used to inhibit the development of PMVM, affecting several aspects of insect's physiology such as the adhesion of T. cruzi epimastigote forms in the midgut (Garcia et al, , 1991Nogueira et al, 1997;Gonzales et al, 1998). Based on the data shown in Fig.…”
Section: Meanmentioning
confidence: 99%
“…Mello et al (2007) observed that the orally treatment of R. prolixus nymphs with the essential oil of Pilocarpus spicatus (Rutaceae) decreased significantly the blood intake in comparison to the control group. Some antifeedant compounds interfere with the perception of feeding stimulants preventing the insects from obtaining the correct taste information, affecting the insect feeding behavior (Garcia et al 1991). However, in our case, the antifeedant effect of carvacrol and thymol against Rhodnius were not strongly enough since only the highest dose of these two compounds led to a decrease in the blood intake when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…By administering 3 consecutive plain blood meals after the treated one, the effect was found to be irreversible in the 5 μg/ml group and only partially reversible at 1 μg/ml. The authors hypothesized that small amounts of azadirachtin may stably bind to various insect organs including brain, prothoracic glands and ovaries and thus interfere with endocrine regulation [ 46 , 47 ]. An irreversible impact on vitellogenesis was also observed by Dhar and colleagues [ 48 ], studying the effects of long-term exposure to neem volatiles on An.…”
Section: Discussionmentioning
confidence: 99%